Inland fisheries 1. Rehabilitation of inland waters for fisheries (FAO RomeIT, 2008)
Covers the policy and economic framework for decisions regarding rehabilitation of inland waters and estuaries. Outlines major technical solutions to rehabilitation of migration pathways and physical structure of the environment.
Keywords: INLAND FISHERY